A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U.S.A., with a key to genera of the subfamily Entocytherinae - Weaver, Patricia G.; Williams, Bronwyn W. (Zootaxa, 2017)
Targeted sampling efforts by the authors for the signal crayfish, Pacifastacus leniusculus, from its native range in the John Day River Basin, Oregon, U.S.A. yielded entocytherid ostracods with a male copulatory complex so clearly different from other entocytherines that a new genus, Aurumcythere gen. nov. is proposed to receive them. This newly proposed, apparently nonsclerotized, genus with hook and spur-like prominences of the posteroventral end of the peniferum is the first new genus of the subfamily Entocytherinae named since Hobbs & Peters described Aphelocythere (= Waltoncythere) in 1977. Aurumcythere gen. nov. represents only the second genus of entocytherid known from the Pacific Northwest. Lack of sclerotization in Aurumcythere gen. nov. provides new insight into poorly understood mating behaviors of entocytherid ostracods.